Magnetic actuation and feedback cooling of a cavity optomechanical torque sensor. Issue 1 (December 2017) - Kim, P.; Hauer, B.; Clark, T.; Fani Sani, F.; Freeman, M.; Davis, J.
Abstract Cavity optomechanics has demonstrated remarkable capabilities, such as measurement and control of mechanical motion at the quantum level. Yet many compelling applications of optomechanics—such as microwave-to-telecom wavelength conversion, quantum memories, materials studies, and sensing applications—require hybrid devices, where the optomechanical system is coupled to a separate, typically condensed matter, system. Here, we demonstrate such a hybrid optomechanical system, in which a mesoscopic ferromagnetic needle is integrated with an optomechanical torsional resonator. Using this system we quantitatively extract the magnetization of the needle, not known a priori, demonstrating the potential of this system for studies of nanomagnetism. Furthermore, we show that we can magnetically dampen its torsional mode from room-temperature to 11.6 K—improving its mechanical response time without sacrificing torque sensitivity. Future extensions will enable studies of high-frequency spin dynamics and broadband wavelength conversion via torque mixing. Although optomechanics enables precision metrology, measurements beyond mechanical properties often require hybrid devices. Here, Kim et al. demonstrate that a ferromagnetic needle integrated with a torsional resonator can determine the magnetic properties and amplify or cool the resonator motion.